PENINGKATAN PENGETAHUAN ANAK PENYANDANG DISABILITAS TERKAIT PELECEHAN SEKSUAL DI SENTRA BUDI PERKASA PALEMBANG - Wagisri, Wagisri; Febrianza, M.; Hakim, Arif Rahman; Hestiriniah, Deby Chintia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
Problems among teenagers are increasing, one of the reasons is the lack of education between parents, guardians and teenagers regarding sexuality. Parents or guardians are the main access for people with disabilities to obtain information and education before entering the school environment. The aim of this community service activity is to increase knowledge and be sensitive to field conditions if problems of sexual harassment, sexual violence, and so on occur. The method used in this activity is a Forum Group Discussion, discussion with exchange of ideas, provision of material and religious lectures. The results of the activities obtained increased the knowledge of parents and teenagers with disabilities about sexuality and juvenile delinquency which must be avoided and controlled. The expected long-term impact is that children and teenagers with disabilities will be able to realize the importance of taking care of themselves, controlling themselves and developing themselves by increasing their knowledge.